Correlates of professional burnout - comparative study of three different high stress occupational groups - Agata Madej (Rozprawy Społeczne)
Abstract The purpose of article is to present the relationship between personality traits, a sense of self-efficacy and the level of stress versus the dimensions of occupational burnout in the group of high-risk occupations.